Antioxidant activities of different parts of Gnetum gnemon L. - Wazir, Dayana; Ahmad, Syahida; Muse, Radzali; Mahmood, Maziah; Abd. Shukor, Mohd. Yunus (Springer Verlag, 2011)
Analyses on biological activities of Gnetum gnemon were done to determine the total phenolic and antioxidants of the plant. Four parts of G. gnemon were used in this study, which were leaf, bark, twig, and seeds of the plant. All parts were extracted in methanol, ethanol, hexane, chloroform and hot water using reflux. The total phenolic content of the plant extracts were determined by using Folin-Ciocalteu method. The results demonstrated that the bark from hot water extract showed the highest total phenolic at 10.71 ± 0.01 mg GAE/ FDW, while the lowest was chloroform extract of seed at 2.15 ± 0.01 mg GAE/ FDW. The antioxidant activity of the plant extracts were determined by using DPPH and FRAP assays, respectively. The DPPH results showed that all plant extracts demonstrated weak free radical scavenging activity tested at the final concentration of 300 μg/ml. In contrast, the methanolic twig extract showed strong reducing power activity (FRAP) at 83.55 ± 1.05%, while the hot water seed extract showed the least activity at 41.86 ± 4.22% tested at the final concentration of 300 μg/ml. However, there were no correlation between total phenolics and both antioxidant assays tested.